Scripted lessons in Papua New Guinea : an investigation into the impact of training on elementary teachers? ability to use them. - Pilgram, Jeffrey (2015)
This study presents the findings from a controlled trial of the new Teacher Guides for English as a subject (n=293) that form part of the new elementary English Standards-Based Curriculum in Papua New Guinea. The aim was to investigate whether training on the Teacher Guides had an impact on teachers’ ability to use and deliver the scripted lessons they contain. The trial was conducted in two provinces. Assessment was by pre- and post-trial questionnaires, reflective journals and focus groups. The multi-arm trial ran over seven weeks with three training groups: group 1, with 1.5 days of full training (n=96), group 2, with 0.5 day of introductory training (n=100), and group 3, (n=97) with no training. Training on the Teacher Guides had no significant effect on adherence to or use of the teaching strategies in the scripted lessons. All groups, regardless of the amount of training they received, reported being able to apply the strategies from the Teacher Guides during lessons. From the pre- and post-trial questionnaires, a significant positive effect in the use of key teaching strategies from using the Teacher Guides was found over time.